Neuromotor performance in infants before and after early open-heart surgery and risk factors for delayed development at 6 months of age. (24th October 2018) - Campbell, Miranda J.; Ziviani, Jenny M.; Stocker, Christian F.; Khan, Asaduzzaman; Sakzewski, Leanne
Abstract: Background: Early identification of infants with CHD at heightened risk of developmental delays can inform surveillance priorities. This study investigated pre-operative and post-operative neuromotor performance in infants undergoing open-heart surgery, and their developmental status at 6 months of age, to identify risk factors and inform care pathways. Methods: Infants undergoing open-heart surgery before 4 months of age were recruited into a prospective cohort study. Neuromotor performance was assessed pre-operatively and post-operatively using the Test of Infant Motor Performance and Prechtl's Assessment of General Movements. Development was assessed at 6 months of age using the Ages and Stages Questionnaire third edition. Pre-operative and post-operative General Movements performance was compared using McNemar's test and test of infant motor performance z-scores using Wilcoxon's signed rank test. Risk factors for delayed development at 6 months were explored using logistic regression. Results: Sixty infants were included in this study. In the 23 (38%) infants. A total of 60 infants were recruited. In the 23 (38%) infants assessed pre-operatively, there was no significant difference between pre- and post-operative performance on the GMs ( p= 0.63) or TIMP ( p= 0.28). At discharge, 15 (26%) infants presented with abnormal GMs, and the median TIMP z-score was −0.93 (IQR: −1.4 to −0.69). At 6 months, 28 (52.8%) infants presented with gross motor delay on the ASQ-3, significantly negatively associated with gestational age ( p= 0.03), length of hospital stay (p=0.04) and discharge TIMP score ( p= 0.01). Conclusions: Post-operative assessment using the GMs and TIMP may be useful to identify infants requiring individualised care and targeted developmental follow-up. Long-term developmental surveillance beyond 6 months of age is recommended.